A Conservative Weight Loss Intervention Relieves Bowel Symptoms in Morbidly Obese Subjects with Irritable Bowel Syndrome: A Prospective Cohort Study - Martin Aasbrenn; Stian Lydersen; Per G. Farup (Journal of Obesity)
Background. Irritable bowel syndrome (IBS) is common in subjects with morbid obesity; the effect of weight loss programs on bowel symptoms is largely unknown. Methods. This prospective cohort study explored bowel symptoms, health scores, and biomarkers in subjects with morbid obesity during a six-month-long conservative weight loss intervention. Bowel symptoms were assessed with IBS-severity scoring system (IBS-SSS) and Gastrointestinal Symptom Rating Scale-IBS. Changes in all variables and associations between the changes in bowel symptoms and the other variables were analysed. Results. Eighty-eight subjects (81% females) were included. Body mass index was reduced from 42.0 (3.6) to 38.7 (3.5) (p<0.001). IBS-SSS was reduced from 116 (104) to 81 (84) (p=0.001). In all, 19 out of 25 variables improved significantly. In subjects with and without IBS at inclusion, the improvement in IBS-SSS was 88 (95% CI 55 to 121) and 10 (95% CI −9 to 29), respectively. Improved bowel symptoms were associated with improved subjective well-being, sense of humour, and vitamin D and negatively associated with reduced body mass index. Conclusion. Body mass index and health scores improved during a conservative weight loss intervention. Subjects with IBS before the intervention had a clinically significant improvement in bowel symptoms.